2001
DOI: 10.1152/ajpgi.2001.281.4.g924
|View full text |Cite
|
Sign up to set email alerts
|

Acid inhibition by intestinal nutrients mediated by CCK-A receptors but not plasma CCK

Abstract: We examined the role of CCK-A receptors in acid inhibition by intestinal nutrients. Gastric acid and plasma CCK and gastrin levels were measured in rats with gastric and duodenal fistulas during intragastric 8% peptone and duodenal perfusion with saline, complete liquid diet (CLD; 20% carbohydrate, 6% fat, and 5% protein), and the individual components of CLD. Acid output was significantly inhibited (50-60%) by CLD, lipid, and dextrose. Plasma CCK was significantly increased by CLD (from 2.6 +/- 0.3 to 4.8 +/-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
2
1
Order By: Relevance
“…Others reported peak levels after SBTI (28,30) or SO (19) to be Ͻ11 pM compared with 20 pM observed in our laboratory. However, basal levels reported in other studies were lower than those observed in the present study (Ͻ1 pM compared with our 8 pM) as were the increases after secretagogue infusion (up to 16-fold compared with our 2.5-fold).…”
Section: Discussioncontrasting
confidence: 57%
“…Others reported peak levels after SBTI (28,30) or SO (19) to be Ͻ11 pM compared with 20 pM observed in our laboratory. However, basal levels reported in other studies were lower than those observed in the present study (Ͻ1 pM compared with our 8 pM) as were the increases after secretagogue infusion (up to 16-fold compared with our 2.5-fold).…”
Section: Discussioncontrasting
confidence: 57%
“…In the oxyntic mucosa, CCK was shown to control histamine release (Chen et al 2004). This mechanism was also demonstrated in the rat (Woltman & Reidelberger, 1999;Lloyd et al 1992Lloyd et al , 2001, in sheep (Zavros & Shulkes, 1997) and in man (Schmidt et al 1994) via occupation of the CCK 2 receptors present on the ECL cells (Modlin & Tang, 1996).…”
Section: Global Effects Of Gastrin and Cholecystokinin In The Gutmentioning
confidence: 83%
“…GRP mediates its effects by gastrin release and it may also be an important neurotransmitter in the vagal–cholinergic pathway, as demonstrated by the GRP antagonist BIM26226, which blocks vagally mediated acid secretion in humans in similar ways to atropine [37]. CCK may also function as a physiologic inhibitor induced by the presence of nutrients in the intestine [38,39]. Other inhibitors of acid secretion that stimulate somatostatin release include glucagon-like peptide, CCK, VIP, leptin, amylin and EGF.…”
Section: Physiology Of Acid Secretionmentioning
confidence: 99%